The Use of Materials in Environmental Sustainability Criteria in Seating Facilities Design Uses the Concept of Metaphor with a Narrative Approach - Cherry Dharmawan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study explains how the application of environmental sustainability criteria with the scope of material efficiency on the concept of metaphor in the design of seating facilities with a narrative approach method. The research is based on the results of UNIKOM students' work in the furniture class in 2021. The research lasted for 4 months. Starting from the pre liminary design stage to the prototype design. The problem of this research is how the narrative approach method to create seating facilities form through the concept of metaphor related to the use of materials in environmental sustainability criteria and the factors that are considered in the selection of materials in environmental sustainability criteria. This research uses a participatory method. Several student works became the object of research. The stages in the design process are making a narrative that functions as a basic design idea, elaborating the narrative, translating the narrative elements on the design in the form of metaphors and using materials. Method Description is used to explain the use of materials in environmental sustainability criteria in the form of seating facilities. The results of the study show that the use of materials in environmental sustainability criteria cannot be fully implemented because they focus on the narrative. Students create forms based solely on narratives using the metaphorical method. However, there are several works that apply the use of materials in environmental sustainability criteria because they are in accordance with the narrative. The concept of metaphor is a tool that translates narration on the idea of a seating facilities design form. The shape created is an original idea from students, students can explore with imagination through narratives and metaphorical concepts, but narratives about environmental sustainability should be considered in creating forms.